2017
DOI: 10.1016/j.biopsych.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance Among Carriers of Pathogenic Copy Number Variants: Analysis of 152,000 UK Biobank Subjects

Abstract: This is the largest study on the cognitive phenotypes of CNVs to date. Adult carriers of neurodevelopmental CNVs from the general population have significant cognitive deficits. The UK Biobank will allow unprecedented opportunities for analysis of further phenotypic consequences of CNVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
247
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 197 publications
(265 citation statements)
references
References 33 publications
15
247
3
Order By: Relevance
“…In contrast, 32 of 39 (82%) (61.5% females, 38.5% males) carrier parents showed mild cognitive, behavioral and/or psychiatric features (Table S5), consistent with previous reports of cognitive impairment and increased risk for schizophrenia in carriers of the 16p12.1 deletion 7,81,82 .…”
Section: Secondary Variants Account For Disease Expressivity In 16p12supporting
confidence: 72%
See 1 more Smart Citation
“…In contrast, 32 of 39 (82%) (61.5% females, 38.5% males) carrier parents showed mild cognitive, behavioral and/or psychiatric features (Table S5), consistent with previous reports of cognitive impairment and increased risk for schizophrenia in carriers of the 16p12.1 deletion 7,81,82 .…”
Section: Secondary Variants Account For Disease Expressivity In 16p12supporting
confidence: 72%
“…For example, in 2002 only 2-3% of autism cases were explained by genetic factors, whereas current studies suggest that rare disruptive mutations, including copy-number variants (CNVs) and singlenucleotide variants (SNVs), account for 10-30% of autism cases [1][2][3][4][5] . Despite initial claims of association with a specific disorder or syndrome, several of these pathogenic variants show incomplete penetrance and variable expressivity [6][7][8][9] . For example, the 16p11.2 BP4-BP5 deletion (OMIM #611913) 10 was first described in children with autism, but further studies on other clinical and population cohorts demonstrated that this deletion is also associated with individuals with intellectual disability and developmental delay (ID/DD), obesity, epilepsy, cardiac disease, and scoliosis, and only about 24% of cases manifest an autism phenotype [10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…The list of 93 pathogenic CNVs was compiled from two widely accepted sources (Coe et al 2014, Dittwald et al 2013) as we have previously reported (Kendall et al 2016). The CNV calls for UK Biobank participants were made in-house as we have previously reported in a UK Biobank CNV study (Kendall et al 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Although the contribution to liability from CNVs at a population level (Purcell et al 2014) is much smaller than that of common alleles, for completeness we also tested whether the frequencies of 93 pathogenic CNVs that have been linked with neurodevelopmental disorders (Coe et al 2014, Dittwald et al 2013, Kendall et al 2016 …”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/160499 doi: bioRxiv preprint first posted online Jul. 7, 2017; this direction, for example deCODE 53 , UK biobank 54 , Geisinger 55 , and the All of Us Research Program (formerly the Precision Medicine Initiative).…”
Section: Strategies To Improve Locus Discovery In Wgsmentioning
confidence: 99%